Characteristics of adipose-derived stem cells isolated from buccal fat pads using CD 271 cell sorting technique - Monsikan Phopetch (Prince of Songkla University, 2023)
Thesis (M.Sc., Oral and Maxillofacial Surgery)--Prince of Songkla University, 2018